123 Comparison of outcomes of patients treated within hours vs out of hours by PPCI for STEMI. (22nd September 2015) - Jones, D A; Rathod, K; Akhtar, M; Guttmann, O; Wicks, E; Jain, A; Mathur, A; Rothman, M T; Knight, C; Wragg, A
Abstract : Background: Primary percutaneous coronary intervention (PPCI) is the treatment of choice for ST-segment elevation myocardial infarction (STEMI) provided PPCI is performed in a timely manner. There is conflicting data regarding the outcomes of patients treated in-hours vs out of-hours, we sought to determine whether in-hospital and long-term outcomes are different among in-hours vs out of hours PPCI patients. Method: Clinical information was analysed from a prospective data base on 1692 STEMI patients who underwent Primary PCI between January 2004 and March 2009 at a London centre. Information was entered at the time of procedure and outcome assessed by all-cause mortality information provided by the Office of National Statistics via the BCIS/CCAD national audit. In hours (IH) was defined as PPCI occurring on weekdays from 0800 to 1700 and out of hours (OFH) was defined as PPCI occurring from 1701 to 0759 during weekdays and anytime on weekends. Results: Of the 1692 patients in the study, 46% (779/1692) underwent out of hours PPCI and 54% (913/1692) in hours. There were no differences in baseline clinical or angiographic characteristics between the two groups (see Abstract 123 Table 1 ). In the overall study group, door-to-balloon times (D2B) were not different (66 min±26 vs 68 min±34, p=0.77). The out of hours patients tended to present later with significantly longer symptom to balloon times (p=0.007). There was a significant difference in MACE between the two groups in favour of those patients treated in hours (7% OFH vs 4% IH, p=0.03) at 30 days, at 1 year (12% OFH vs 7% IH, p=0.002) and at 3 years (13% vs 9%, p=0.02) MACE was driven by increase in mortality, myocardial infarction and TVR in the out of hours group. Conclusion: STEMI patients have worse clinical outcomes if treated out of hours by PPCI. This observation does not appear related to PCI centre door to balloon times. Further research is needed to understand and improve the causes of the worse outcomes out of hours.